**Answer:**

A

**Step-by-step explanation:**

Given the 2 equations

2x + y = 13 → (1)

x - y = - 4 → (2)

Add the 2 equations term by term to eliminate the y- term, that is

3x = 9 ( divide both sides by 3 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Substituting into (1)

2(3) + y = 13

6 + y = 13 ( subtract 6 from both sides )

y = 7

solution is (3, 7 ) → A

**Answer:**

Answer would be 9y+36

**Step-by-step explanation:**

Because if you distribute the 9 inside the parenthesis, you'd get

9*y=9y and 9*4=36

so 9y+36

Hope my answer was helpful to you!

**Answer:**

y=1

**Step-by-step explanation:**

there is no slope therefore dont place it. however there is a Y intercept.

**Answer:**

:) The Inverse of the Function f(x) = 2x + 1 is f-1(x) = x/2 - 1/2.

**Step-by-step explanation:**

mark me brainlist^_^

**Answer:**

B. y = -16

**Step-by-step explanation:**

Vertical line means x is zero and y is anything but zero. In the coordinates, (x,y), -16 is y so the vertical line is -16.